Is There a Role for Surgical Resection of Multifocal Glioblastoma? A Retrospective Analysis of 100 Patients. Issue 6 (18th October 2021) - Friso, Filippo; Rucci, Paola; Rosetti, Vittoria; Carretta, Alessandro; Bortolotti, Carlo; Ramponi, Vania; Martinoni, Matteo; Palandri, Giorgio; Zoli, Matteo; Badaloni, Filippo; Franceschi, Enrico; Asioli, Sofia; et al.
Abstract: BACKGROUND: Glioblastoma with multiple localizations (mGBMs) can be defined as multifocal, where enhancing lesions present a connection visible on magnetic resonance imaging fluid-attenuated inversion recovery imaging, or multicentric, in the absence of a clear dissemination pathway. OBJECTIVE: To evaluate the role of the extent of resection (EOR) in the treatment of mGBMs and its correlation with overall survival (OS) and progression free survival (PFS). METHODS: One hundred patients with mGBMs were treated at our Institution between 2009 and 2019. Clinical, radiological, and follow-up data were collected. EOR of the contrast-enhancing part of lesions was classified as gross total resection (GTR, absence of tumor remnant), subtotal resection (STR, residual tumor < 30% of the initial mass), partial resection (PR, residual tumor > 30% of the initial mass), and needle or open biopsy (residual tumor > 75% of the initial mass). RESULTS: Approximately 15% of patients underwent GTR, 14% STR, 32% PR, and 39% biopsy. Median OS was 17 mo for GTR, 11 mo for STR, 7 mo for PR, and 5 mo for biopsy. Greater EOR was associated with a significantly longer OS than biopsy. GTR and STR were associated with a longer PFS in Kaplan-Meier survival analyses. After adjusting for age, Karnofsky performance status (KPS), number of lesions, and adjunctive therapy in multivariable Cox regression analyses, GTR, STR, and PR were still associated with OS, but only GTR remained associated with PFS. CONCLUSION: Our study suggests that EOR may positively influence survival of patients with mGBM. Surgical resection can be a reasonable option when performance and access to adjuvant treatment can be preserved. Graphical Abstract: